Reproductive Biology of the Egyptian Sabaraus Crenidens Crenidens (Forsskal, 1775), in the Libyan Eastern Coast, Libya - EL-MOR, Mohammad EL-SAYED (Al-Mukhtar Journal of Sciences, 2008)
The reproductive biology of Crenidens crenidens, (family: Sparidae) a Lessepsian migrant species inhabiting Libyan eastern coast was studied. There were monthly variation in sex ratio, and a tendency for more females (559 fish, 50.7%) than males (544 fish, 49.3%) for the whole population. Overall sex ratio was 1: 1.03 for males to females. The male of Crenidens crenidens attained its first maturity at the totals length of 14.0 cm., while the first sexual maturity of female was attained at 15.4 cm. The gonado-somatic indexes of males was lower than that of females. Males and females have a definite breeding season which extends from November till February. In March and April, Crenidens crenidens population migrated from the Libyan eastern coast for spawning elsewhere. An increase in oocyte diameters was evident in September (with an average of 233 µ) and this increase continued in the following months till February, with an average value of 482µ. The absolute fecundity ranged from 678 to 9888 with length ranging from 13.5 to 22.6 cm. Also, fecundity increased from 755 to 9888 with increasing the weight from 26.7 to 112.9 gm.